The heart of vocal harmony : emotional expression in group singing - Sharon, Deke. (Milwaukee, WI : Hal LEonard Books, 2016)
Most choirs spend their rehearsal time focusing on notes, rhythms, and precision. They rarely, if ever, discuss a song's meaning and feeling, even though those elements are precisely what draws people to vocal music in the first place. Thousands of books have been written about choral technique, teaching people how to sing technically well. What sets The Heart of Vocal Harmony apart is its focus on honest unified expression and the process of delivering an emotionally compelling performance. It delves into this underdeveloped vocal topic: the heart of vocal music and the process involved in consistent emotional expression while singing as a group. The Heart of Vocal Harmony is not just for a cappella groups-it is for all vocal harmony groups, ensembles, and choirs of all levels, with or without instruments. In addition to the process, the book features discussions with some of the biggest luminaries in vocal harmony: composers, arrangers, directors, singers, and groups-including Eric Whitacre, Pentatonix, the Manhattan Transfer, and more!
Concepts. Basic principles ; Say something ; Singularity -- Preparations. Setting the stage ; Harmony through harmony ; Director ; Intragroup relationships ; Safety ; Openness ; Bravery ; Support ; Size and scope ; Breaking down barriers ; Facial connectedness -- Emotions. Definition ; Joy ; Anger ; Fear ; Sadness ; Emotional complexity -- Choices. Appropriateness ; Song ; Solo ; Presentation ; Arrangement -- Meanings. Depth ; Lyrical analysis ; Context ; Group discussion -- Perspectives. Living the song ; Identification ; Visualization ; Character ; Substitution ; Plot ; Moment ; Triggers -- Techniques. Emotional-technical connection ; Thresholds ; Actor's techniques ; First time ; Purpose ; Singing by memory ; Foreign languages ; Vocal tone ; Syllables ; Repetition ; Autopilot ; The spaces between -- Considerations. Importance of the individual ; Rehearsal consistency ; Empowering language ; The right words ; Eroding inhibitions ; Emotional intelligence ; Inner critic ; Physicality ; Priorities ; Calibration ; Overboard ; Overwhelm ; Recharge -- Motivations. Musical motivation ; Performing as director ; Leading from the front ; Lead vocal ; Powerful moments -- Insights. Composers ; Arrangers ; Directors ; Vocal coaches ; Groups ; Singers.
Includes bibliographical references.
Keywords: Choral singing -- Instruction and study; Emotions in music